Prevalence and Data Transparency of National Clinical Registries in the United States. Issue 4 (July 2016) - Lyu, Heather; Cooper, Michol; Patel, Kavita; Daniel, Michael; Makary, Martin A.
Abstract : Objective: To determine the prevalence and characteristics of national clinical registries. Methods: Review of clinical registries through the following: (1) PubMed search using MeSH term "registries, " (2) clinical trials database search using the term "registry, " (3) review of the American Medical Association (AMA) recognized specialty societies for registry affiliation, and (4) consultation with a panel representing the American Board of Medical Specialties (ABMS). Main Outcome Measures: Outcomes that characterize registries (type, participants, specialty affiliation, funding), reflect data quality (risk adjustment, auditing practices), and indicate transparency (public reporting). Results: We identified 153 clinical registries of which 47.7% (73) were health services registries, 43.1% (66) were disease registries, and 9.2% (14) were combination registries. The mean number of hospitals per registry was 1, 693 (interquartile range [IQR] = 45–230), and the mean number of patients per registry was 1, 160, 492 (IQR = 2, 150–10, 045). Among the 117 AMA specialty societies, 16.2% (19) were affiliated with a registry. Government funding was associated with 26.1% (40/153) of registries. Of the 153 registries, 23.5% (36) risk adjusted outcomes and 18.3% (23) audited data. Mandatory public reporting of hospital outcomes for all participating hospitals was associated with 2.0% (3/153) of registries. Conclusion: There is substantial opportunity to develop more specialty-specific clinical registries with publicly available data.